Manipulation of precipitation and mechanical properties of precipitation-strengthened medium-entropy alloy - Lv, Jiwei; Yu, Haoyang; Fang, Wei; Yin, Fuxing; Wei, Daixiu (Scripta materialia, 2023)
Medium-entropy alloys (MEAs) strengthened by coherent L12 precipitates were recently developed. However, incoherent precipitates are often unexpectedly formed owing to the composition complexity. Their regulation needs to be elucidated. In this study, we clarify the influence of prestrain-induced dislocations on the formation of both L12 and L21 precipitates in the most representative precipitation-strengthened (FeCoNi)86Ti7Al7 MEA. The formation of incoherent L21 precipitates was promoted by the prestrain. Their amount was increased, while their size was refined by the prestrain before isothermal aging. The formation of the coherent L12 precipitates was indistinctively affected by the prestrain. Consequently, the room-temperature tensile properties were improved. A tensile yield strength of 1127 MPa, ultimate tensile strength of 1369 MPa, and satisfactory tensile elongation of 11.2% were obtained. This study provides insights into the regulation of the formation of incoherent precipitates and optimization of the mechanical performances of precipitation-strengthened alloys. [Display omitted]